Bicuspid aortic valve with critical coarctation of the aorta: singleor two-stage operation? - Zhang, Hongqiang; Zhu, Kai; Yang, Shouguo; Zhai, Junyu; Zhou, Tianyu; Sun, Xiaoning; Wang, Chunsheng (Journal of Thoracic Disease; Vol 10, No 7 (July 31, 2018): Journal of Thoracic Disease, 2018)
Background: A bicuspid aortic valve (BAV) with critical coarctation of the aorta (CoA) is a rare but dangerous congenital cardiac malformation. The aim of this study was to compare the beneﬁts of a single- versus two-stage operation for patients of BAV with CoA. Methods: We retrospectively evaluated 20 patients of BAV and CoA who underwent surgery from 2000 to 2016 in our center. Eight patients underwent a single-stage procedure through a median sternotomy approach, while 12 patients underwent two-stage operation. Results: The patients’ baseline characteristics were similar between the two groups, and the overall mortality rate was 0%. No signiﬁcant differences were found in the postoperative pressure gradient (P=0.64), use of implants (P=0.81), reoperation for bleeding, phrenic nerve injury, blood transfusion (P=1.00), or thromboembolic events between the two groups. However, patients in the single-stage group sustained less surgical trauma and ICU stay hours (P